Politics of on-demand food delivery: policy design and the power of algorithms - Chou, Meng-Hsuan (2023)
In this article, we examine the politics of on-demand food delivery using insights from the theory of social construction and policy design. On-demand food delivery is a service built on algorithm-based technology known for its precarity and physical risks for couriers. We compare how the on-demand food delivery sector is regulated and its observable effects in two Asia-Pacific cities with contrasting food courier profiles: Melbourne, Australia (international students), and Singapore (citizens, permanent residents). We show how the social construction of food couriers in other policy subsystems (migration, higher education, citizenship) affects debates of their fair treatment in the on-demand food delivery sector. By interrogating the politics of digitally enabled versions of reality, we argue for embracing a design perspective to identify how reforms could be introduced in change-resistant sectors.